1990
DOI: 10.1038/ki.1990.234
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II receptor regulation in anti-glomerular basement membrane nephritis

Abstract: The expression of the glomerular receptor for angiotensin II (Ang II-R) was examined longitudinally following the induction of anti-glomerular basement membrane (GBM) nephritis in the rat. The specific aim of the project was to determine whether immunologically-induced glomerular injury led to significant abnormalities of the relationship between glomerular Ang II-R and its circulating ligand, Ang II. Scatchard analysis was used to measure Ang II-R on purified glomeruli at selected time intervals over two mont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

1993
1993
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 19 publications
0
17
0
Order By: Relevance
“…Therefore, MC could be one of the major targets of the AngII effect. Indeed, as a consequence of mesangial contraction by AngII, a significant decrease in glomerular plasma flow and single nephron glomerular filtration rate, followed by increased renal vascular resistance, was observed in this model in a dose-dependent manner (15,17). Consequently, one can postulate that excessively elevated AngII may elicit increased intracellular calcium levels in MC and subsequently a wide variety of cellular responses by a Ca 2ϩ -dependent pathway.…”
Section: Angii Exerts Proinflammatory Effects In the Kidney Partly Tmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, MC could be one of the major targets of the AngII effect. Indeed, as a consequence of mesangial contraction by AngII, a significant decrease in glomerular plasma flow and single nephron glomerular filtration rate, followed by increased renal vascular resistance, was observed in this model in a dose-dependent manner (15,17). Consequently, one can postulate that excessively elevated AngII may elicit increased intracellular calcium levels in MC and subsequently a wide variety of cellular responses by a Ca 2ϩ -dependent pathway.…”
Section: Angii Exerts Proinflammatory Effects In the Kidney Partly Tmentioning
confidence: 99%
“…Besides, different T cell responses between ␥W and ␥A chimeras indicate that their bone marrow-derived glomerular resident cells (49) (presumably FcR Ϫ but AT1 ϩ ) may not play an important role for T cell recruitment. In this disease, dose-dependent activation of intrarenal and systemic RAS has been demonstrated (15)(16)(17). AngII has some cellular effects on most tissues, mainly via AT1, that may contribute to the disease pathogenesis (11,19), and also regulates cellular immunity by acting on the proliferation of splenic lymphocytes (20).…”
Section: Renal Ras Activation Conducts Glomerular T Cell Responsementioning
confidence: 99%
See 2 more Smart Citations
“…Some investigators have reported the activation of the RAS in the acute phase of anti-GBM nephritis, suggesting the role of AII (12,13). However, the pathogenic role of AII has not been established.…”
Section: Introductionmentioning
confidence: 99%